ANALISIS AKTIVITAS CORPORATE SOCIAL RESPONSIBILITY (CSR) PT BUKAKA TEKNIK UTAMA TBK MELALUI PROGRAM BEASISWA BOGOR EDUCARE - Azkiya Mentari Putri (2023)
This research is motivated by the implementation of the Bogor EduCARE scholarship program as one of the CSR activities of PT Bukaka Teknik Utama Tbk. This program helps improve education in the community through competent human resources. The program is one of the company's contributions in helping realize the SDGs goals on education indicators in Indonesia. This study used a qualitative method and the type of research used was descriptive with a case study method with data collection through interviews and literature studies. The theory used in this research is Attribution Theory. The data collected in this study are in the form of primary data and secondary data. The primary research data is through interviews, documentation and literature studies. And secondary research data, namely through library research and previous research. Interviews were conducted by selecting informants related to the company's CSR program. The data analysis techniques used in this study are data collection techniques, data reduction, data presentation, conclusions and data verification. The purpose of this study is to find out CSR activities in helping SDGs on educational indicators through the Bogor EDuCARE scholarship program. The results of this study describe that the Bogor EduCARE scholarship program run by PT Bukaka Teknik Utama Tbk using a social responsibility approach helps improve the quality of education so that it influences the realization of the goals of the SDGs indicator of education in Indonesia. That the process of this CSR program is Bogor EduCARE with the aim of helping people who have the desire to continue their education but are constrained financially.